Rising food prices - causes, implications, and challenges for development policy - Michael Brüntrup (Deutsches Institut für Entwicklungspolitik (DIE), 2008)
For several months now, worldwide food prices have exploded. This has had severe impacts on many developing countries, ranging from increases in poverty and hunger and problems with inflation and balances of payment to national instabilities. The extreme price boom is likely to prove more shortterm in character. However, there are a number of longer-term trends that appear to indicate a tendency toward food prices higher and more unstable than they have been in the past. While in the short term the ongoing food crisis is harmful to most urban and rural households, viewed in the longer-term perspective, (moderately) higher prices have positive effects on the majority of rural households, and thus on poverty as well, which continues to be a mainly rural phenomenon. Both governments and development policy are urgently called upon to adopt short-term measures, including e.g. an easing of import and export restrictions, provision of import or consumer credits, direct transfers, and, possibly, food aid, designed to quickly defuse situations that may often be explosive. But there is also a need for longer-term measures designed to promote agriculture in developing countries -, on the one hand to boost output and thus to return food prices to tolerable levels and stabilize them and on the other hand to bolster rural economic cycles and sustainably raise the purchasing power of the rural population.
Keywords: 330